Adhesive hydrogel / high-moisture-absorption carbon fiber felt composite material as well as preparation method and application thereof

Through needle puncture treatment, the carbon fiber felt is improved and combined with the adhesion hydrogel is solved, and the problem of insufficient flexibility and thermal conductivity of the lithium battery thermal management materials is achieved, achieving efficient heat dissipation performance and thermal stability.

CN119610738APending Publication Date: 2025-03-14SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411725919.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lithium battery thermal management materials have shortcomings in terms of flexibility and mechanical strength, making it difficult to flexibly wrap batteries of different shapes. The traditional heat dissipation materials have low thermal conductivity and large interface thermal resistance, which affects the cooling effect.

Method used

Adhesive hydrogel/high-hygroscopic carbon fiber felt composite material is used to improve the out-of-plane thermal conductivity of the carbon fiber felt through needle puncture treatment, and is combined with the adhesive hydrogel to increase the thermal conductivity and adhesion of the material.

Benefits of technology

It achieves high out-of-plane thermal conductivity, leakage prevention and high adhesion, has excellent heat dissipation performance and thermal stability, maintains shape stability in high temperature and ultra-low temperature environments, and significantly reduces the temperature of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119610738A_ABST
    Figure CN119610738A_ABST
Patent Text Reader

Abstract

The invention discloses an adhesive hydrogel / high-moisture-absorption carbon fiber felt composite material and a preparation method and application thereof.According to the adhesive hydrogel / high-moisture-absorption carbon fiber felt composite material and the preparation method and application thereof, needled carbon fiber felt with high out-of-plane thermal conductivity serves as a base material, and the out-of-plane thermal conductivity of the needled carbon fiber felt is improved by increasing the needling density and improving the orientation degree of carbon fibers in the out-of-plane direction. A three-dimensional skeleton structure formed by the flatly laid fiber net in the needled carbon fiber felt and the fiber bundles in the thickness direction is beneficial to avoiding the leakage problem in the moisture absorption process, adsorbed water is stably bound in a fiber skeleton, and the needled carbon fiber felt shows huge potential in the aspect of battery heat dissipation application. The adhesive hydrogel / high-moisture-absorption carbon fiber felt composite material prepared by the invention has high out-of-plane thermal conductivity, leakage resistance and high adhesion, has excellent heat dissipation performance and thermal stability, and can keep shape stability in high-temperature and ultralow-temperature environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat dissipation materials, and in particular to an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material and a preparation method and application thereof. Background Art

[0002] With the increase in lithium battery capacity and the acceleration of charge and discharge rates, the thermal management problem of batteries has become increasingly prominent. Lithium batteries generate a lot of heat during the charge and discharge process. If the heat is not dissipated in time, the battery temperature will be too high, affecting its performance, life and safety. Therefore, the development of efficient thermal management materials has become a key task in the development of lithium battery technology. In the thermal management system of lithium batteries, the traditional active cooling strategy is an important means to ensure the safe operation of batteries under high temperature conditions. The air cooling system dissipates heat through airflow, but there are problems such as low cooling efficiency and uneven temperature distribution; the liquid cooling system achieves uniform heat dissipation through the circulation of coolant, but the cost is high, the design is complex, and there is a potential risk of leakage. In recent years, phase change materials (PCMs) have gradually been used in lithium battery thermal management systems due to their advantages of fast response, uniform temperature control and near-zero energy consumption, especially organic solid-liquid PCMs (such as paraffin), which have been widely studied due to their large latent heat storage performance. However, the thermal conductivity of this type of material is low. Researchers have improved the thermal conductivity by introducing high thermal conductivity additives (such as graphene, boron nitride) or three-dimensional thermal conductive structures.

[0003] Compared with solid-liquid PCMs, liquid-gas PCMs have a more significant advantage in cooling performance due to their higher latent heat of phase change (about 2400 J / g when water evaporates). New passive thermal management materials based on water evaporation have been studied, in which hygroscopic salts, metal organic frameworks (MOFs) and other adsorbents are doped into porous materials (such as expanded graphite and thermally conductive aerogels), and efficient cooling can be achieved by dissipating heat through water desorption. However, battery thermal management materials often require high flexibility and mechanical strength to reduce thermal contact resistance. Due to the low mechanical modulus and limited adhesion, thermally conductive tape or silicone resin is often used to fill the gap between the battery and the heat dissipation material, but this will increase the interfacial thermal resistance and affect the cooling effect. At present, although commonly used materials such as expanded graphite, thermally conductive aerogel and thermally conductive sponge have good thermal conductivity, they are insufficient in flexibility and are difficult to flexibly wrap batteries of different shapes, thereby limiting their application in a variety of battery structures. Therefore, the research and development of self-adhesive heat dissipation materials is still very challenging. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material and a preparation method and application thereof.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material comprises the following steps:

[0007] (1) performing a needle punching treatment on the carbon fiber felt to obtain a carbon fiber felt in an out-of-plane direction;

[0008] (2) compounding the adhesive hydrogel with the carbon fiber felt in the out-of-plane direction obtained in step (1) to obtain an adhesive hydrogel / carbon fiber felt composite material;

[0009] (3) coating a hygroscopic salt solution on one side of the carbon fiber felt of the adhesive hydrogel / carbon fiber felt composite material obtained in step (2), drying it and then subjecting it to a hygroscopic treatment to obtain the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material.

[0010] The present invention utilizes a needle punching process to increase the needle punching density of a carbon fiber felt to obtain a carbon fiber felt with a high out-of-plane orientation, composites the carbon fiber felt with a high out-of-plane orientation with a prepared strong adhesive hydrogel, and sprays a hygroscopic salt solution on one side of the carbon fiber felt to obtain an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material. The adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared by the present invention has high out-of-plane thermal conductivity, anti-leakage and high adhesion, excellent heat dissipation performance and thermal stability, and can maintain shape stability in high temperature and ultra-low temperature environments.

[0011] Furthermore, in step (1), the carbon fibers in the carbon fiber felt in the out-of-plane direction have a high orientation in the out-of-plane direction, and the out-of-plane direction refers to a direction perpendicular to the surface of the carbon fiber felt.

[0012] Furthermore, in step (1), a needle punching process is used to increase the needle punching density of the carbon fiber felt to obtain a carbon fiber felt with a high out-of-plane orientation.

[0013] Furthermore, in step (1), the needle punching density of the carbon fiber felt in the out-of-plane direction is 20-41 needles / cm 2 , preferably 32-36 thorns / cm 2 .

[0014] Furthermore, in step (1), the in-plane thermal conductivity of the carbon fiber felt in the out-of-plane direction is 2.0-2.4 W·m -1 ·K -1 , the out-of-plane thermal conductivity is 0.84-0.88W·m -1 ·K -1 , indicating that it has excellent thermal conductivity and effectively improves the out-of-plane thermal conductivity; the water content at 70% ambient humidity is 1.6-1.64g·g -1, indicating that it has excellent hygroscopicity; when used for lithium battery heat dissipation, the lithium battery temperature can be reduced by up to 21-23°C during the 10C ultra-high discharge rate process, indicating that at ultra-high discharge rate, high out-of-plane orientation carbon fiber felt has excellent battery evaporation heat dissipation performance and no leakage during the charging and discharging process.

[0015] Furthermore, in step (2), the adhesive hydrogel contains a high thermal conductivity nanofiller and has water retention during long-term storage.

[0016] Furthermore, in step (2), the thickness of the adhesive hydrogel is 0.5-1.5 mm, and the thickness of the carbon fiber felt in the out-of-plane direction is 3-4 mm.

[0017] Furthermore, in step (2), the method for preparing the adhesive hydrogel comprises the following steps:

[0018] S1. Dissolving acrylic acid and chitosan quaternary ammonium salt in glycerol or a mixed solvent of an ionic liquid and water to obtain a mixed solution;

[0019] S2. Adding a carbon-based thermally conductive filler, a thermal initiator and a cross-linking agent to the mixed solution obtained in step (1), performing a heating polymerization reaction, and obtaining the adhesive hydrogel.

[0020] Furthermore, in S1, the molar ratio of acrylic acid to chitosan quaternary ammonium salt is (10-20):1.

[0021] Furthermore, in S1, in the mixed solvent of glycerol and water, glycerol accounts for 15%-35% of the volume of the mixed solvent.

[0022] Furthermore, in S1, in the mixed solvent of the ionic liquid and water, the ionic liquid accounts for 15%-35% of the volume of the mixed solvent.

[0023] Furthermore, in S1, the ionic liquid may be 1-butyl-3-methylimidazolium chloride.

[0024] Furthermore, in S1, acrylic acid and chitosan quaternary ammonium salt are dissolved in glycerol or a mixed solvent of ionic liquid and water, and stirred for 20-40 minutes to obtain a mixed solution.

[0025] Further, in S2, the carbon-based thermally conductive filler, the thermal initiator and the cross-linking agent are added to the mixed solution and stirred for 10-20 minutes.

[0026] Furthermore, in S2, the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt in the mixed solution to the thermal initiator is 1:(0.001-0.002).

[0027] Furthermore, in S2, the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt in the mixed solution to the cross-linking agent is 1:(0.001-0.002).

[0028] Furthermore, in S2, the mass ratio of the carbon-based thermally conductive filler to the mixed solution is (0.1-0.2):100.

[0029] Furthermore, in S2, the carbon-based thermally conductive filler is carbon nanotubes, the thermal initiator is ammonium persulfate, and the cross-linking agent is methylenebisacrylamide.

[0030] Furthermore, in S2, the temperature of the heating polymerization reaction is 60-80°C and the time is 5-7h.

[0031] In a specific embodiment, the adhesive hydrogel is prepared by the following method: acrylic acid and chitosan quaternary ammonium salt are added to a mixed solvent of glycerol and water to obtain a uniform mixed solution, and then a carbon-based thermal conductive filler, a thermal initiator and a cross-linking agent are added thereto, and after stirring evenly, the mixture is poured into a mold and heated for a period of time to obtain the adhesive hydrogel.

[0032] Furthermore, in step (3), the concentration of the hygroscopic salt in the hygroscopic salt solution is 10-30 wt%.

[0033] Furthermore, the hygroscopic salt is lithium chloride or calcium chloride, or may be a metal organic framework (MIL-101(Cr)).

[0034] Furthermore, in step (3), the hygroscopic salt solution is prepared by dissolving a hygroscopic salt in a mixed solvent of ethanol and water.

[0035] Furthermore, in the mixed solvent of ethanol and water, ethanol accounts for 20-60% of the volume of the mixed solvent.

[0036] Furthermore, in step (3), the hygroscopic salt loading on the carbon fiber felt is 1.3-1.5 g·g -1 .

[0037] Furthermore, in step (3), the drying treatment is carried out at a temperature of 80-90° C. and for a time of 2-3 hours.

[0038] Furthermore, in step (3), the moisture absorption treatment is performed at an ambient humidity of 70 to 90% to fully absorb moisture.

[0039] Furthermore, in step (3), the moisture absorption treatment time is 10-12 hours.

[0040] The present invention protects an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared by the method.

[0041] The adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared by the present invention has evaporative heat dissipation and adhesion effects, and the in-plane thermal conductivity is 2.66-2.70 W·m -1 ·K -1 , the out-of-plane thermal conductivity is 0.79-0.83W·m -1 ·K -1 , has excellent thermal conductivity; the hygroscopicity (water content) at 70% ambient humidity is 0.80-0.82g·g -1 When used for lithium battery heat dissipation, the temperature of the lithium battery was reduced by 27-29°C at an ultra-high discharge rate of 10C, indicating that the composite material further improved the evaporative heat dissipation performance at ultra-high discharge rates. During the 100-cycle charge and discharge test, the average maximum temperature was reduced by 25-27°C, indicating that the composite material has stable and recyclable evaporative cooling performance. At different discharge rates of 2-10C, the heat dissipation efficiency is as high as 50.0%-53.9%, which is significantly better than other reported evaporative heat dissipation materials (24.7%-44.6%).

[0042] The present invention also protects the application of the above-mentioned adhesive hydrogel / highly hygroscopic carbon fiber felt composite material in the field of heat dissipation of electronic devices, such as for heat dissipation of batteries.

[0043] The excellent heat dissipation performance of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material provided by the present invention can be attributed to the strong adhesion and the evaporation of a large amount of water, which extracts and releases heat into the environment. Once the battery heat accumulates, the saturated vapor pressure of the composite surface affected by temperature increases, and the adsorption equilibrium point decreases accordingly, resulting in water desorption. During the evaporation process, some water molecules with greater kinetic energy can overcome the attraction of neighboring water molecules and continue to diffuse into the air, thereby taking away the latent heat and cooling the battery. At the same time, when the battery is not working, the partially dehydrated composite material will spontaneously absorb moisture from the environment and store it inside, realizing a long-term circulation cooling function. For actual heat and mass transfer, in addition to evaporative heat dissipation, the heat dissipation methods for the battery also include heat conduction, heat radiation and heat convection. The heat generated by the battery is rapidly conducted to the low-temperature area of ​​the composite material under the action of the adhesive hydrogel, and the increase in the out-of-plane thermal conductivity further enhances the diffusion and conduction of heat along the direction of the carbon fiber bundle. At the same time, the surface of the composite material transfers heat to the low-temperature environment by convective heat exchange. Since the carbon fiber felt has a high emissivity, its surface thermal radiation also promotes the heat dissipation of the battery.

[0044] Beneficial effects of the present invention:

[0045] 1. The present invention adopts a needle-punched carbon fiber felt with high out-of-plane thermal conductivity as a substrate, and improves the out-of-plane thermal conductivity of the needle-punched carbon fiber felt by increasing the needle-punching density and improving the orientation of the carbon fibers in the out-of-plane direction. The three-dimensional skeleton structure formed by the flat fiber web and the fiber bundles in the thickness direction in the needle-punched carbon fiber felt helps to avoid leakage problems during moisture absorption, and the adsorbed water is stably bound in the fiber skeleton, showing great potential in battery heat dissipation applications. Acrylic acid and chitosan quaternary ammonium salt are used as monomers to prepare hydrogels with stable strong adhesion. An appropriate amount of carbon-based thermally conductive filler in the adhesive hydrogel improves the thermal conductivity and thermal stability of the hydrogel. The addition of glycerol gives the adhesive hydrogel stable shape stability and water retention under high and ultra-low temperature environments.

[0046] 2. The present invention uses carbon fiber felt as a base material for modification. The carbon fiber felt is green and environmentally friendly, has high porosity, high thermal conductivity and flame retardancy, and can be mass-produced. The present invention uses needle punching treatment to improve the out-of-plane thermal conductivity of the carbon fiber felt, thereby further improving the heat dissipation performance.

[0047] 3. The present invention uses adhesive hydrogel and high out-of-plane orientation carbon fiber felt to reduce the interfacial thermal resistance between the heat dissipation material and the battery and improve the heat dissipation. At the same time, an appropriate amount of high thermal conductivity nanofiller is used to increase the thermal conductivity and thermal stability of the hydrogel. An appropriate amount of glycerol is used to give the hydrogel excellent shape stability and water retention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a flow chart for preparing the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material in Example 1.

[0049] Figure 2 These are the SEM and EDS images of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2.

[0050] Figure 3 1 is a rheological test graph of the adhesive hydrogel in Example 2; wherein a is a rheological test graph of the adhesive hydrogel changing with shear frequency, and b is a rheological test graph of the adhesive hydrogel changing with temperature.

[0051] Figure 4 This is a graph showing the adhesion test results of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 to different substrate materials.

[0052] Figure 5 This is a graph showing the environmental stability test results of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2.

[0053] Figure 6This is a graph showing the hygroscopicity test results of the high out-of-plane orientation carbon fiber felt prepared in Example 2 at different hygroscopic salt loadings.

[0054] Figure 7 This is a graph showing the hygroscopicity data of highly out-of-plane oriented hygroscopic carbon fiber felt under different ambient humidity.

[0055] Figure 8 This is a graph showing the hygroscopicity data of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 under different ambient humidity.

[0056] Fig. 9 This is a graph showing the desorption data of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 under different ambient humidity.

[0057] Fig.10 These are the contact angle test graphs of the surface and peeling surface of the high out-of-plane orientation hygroscopic carbon fiber felt prepared in Example 2, as well as the leakage resistance test result graph of the high out-of-plane orientation hygroscopic carbon fiber felt; wherein, a is the contact angle test graph of the surface and the peeling surface, and b is the leakage resistance test result graph.

[0058] Fig.11 This is a distribution diagram of surface needle punching points of carbon fiber felt at different needle punching densities in Examples 2-5.

[0059] Fig.12 The interlayer peeling surface morphology and corresponding 3D contour diagram of the carbon fiber felt at different needle punching densities in Examples 2-5.

[0060] Fig.13 This is a graph of thermal conductivity of hygroscopic carbon fiber felts of Examples 2-5 at different needle punching densities.

[0061] Fig.14 This is a data graph of the heat dissipation of carbon fiber felt at different needle punching densities in Examples 2-5.

[0062] Fig.15 This is a data graph of the heat dissipation of hygroscopic carbon fiber felts of Examples 2-5 at different needle punching densities.

[0063] Fig.16 This is a graph showing the tensile breaking strength test results of the carbon fiber felts with different needle punching densities prepared in Examples 2-5.

[0064] Fig.17 This is a schematic diagram of a lithium battery wrapped with the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2.

[0065] Fig.18Temperature change curves of batteries wrapped with carbon fiber felt in Example 2, adhesive hydrogel with / without carbon nanotubes added (adhesive hydrogel-without carbon nanotubes and adhesive hydrogel-with carbon nanotubes), highly hygroscopic carbon fiber felt and adhesive hydrogel / high hygroscopic carbon fiber felt composite material at a discharge rate of 10C.

[0066] Fig.19 This is a temperature change curve of batteries wrapped and unwrapped with the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 at different discharge rates.

[0067] Fig. 20 This is a comparison chart of the evaporative cooling efficiency of the adhesive hydrogel / highly hygroscopic carbon fiber felt battery heat dissipation material prepared in Example 2 and the composite material in the prior art on the battery at different discharge rates.

[0068] Fig.21 The temperature variation curve of the battery wrapped and not wrapped with the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 during 100 cycles of charge and discharge.

[0069] Fig. 22 This is a graph showing the flame retardancy test results of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 under flame combustion.

[0070] Fig.23 The thermogravimetric graphs of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material, high out-of-plane orientation carbon fiber felt and adhesive hydrogel prepared in Example 2 under air atmosphere. DETAILED DESCRIPTION

[0071] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0072] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0073] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0074] In the following embodiments, the battery is a commercial 18650-3.7V / 2.0Ah lithium battery; the heat dissipation performance of the battery is tested using a laboratory battery testing system (NEWARE, CT-4008-5V30A).

[0075] Example 1

[0076] A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material, such as Figure 1 As shown, the following steps are included:

[0077] (1) The carbon fiber felt is needle-punched with a needle-punching density of 32 needles / cm 2 , a high out-of-plane orientation carbon fiber felt with a thickness of 3 mm was obtained.

[0078] (2) dissolving acrylic acid and chitosan quaternary ammonium salt (molar ratio of 10:1) in a mixed solvent of glycerol and water (glycerol accounts for 15%), stirring for 40 minutes to obtain a mixed solution; adding carbon nanotubes, ammonium persulfate and methylenebisacrylamide to the mixed solution, stirring for 10 minutes to obtain a mixed solution to be polymerized; wherein the mass ratio of carbon nanotubes to the mixed solution is 0.1:100, the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt to ammonium persulfate is 1:0.001, and the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt to methylenebisacrylamide is 1:0.001; pouring the mixed solution to be polymerized into a mold, heating at 60°C for 7 hours, and obtaining an adhesive hydrogel with a thickness of 0.5 mm.

[0079] (3) Compounding the carbon fiber felt with high out-of-plane orientation obtained in step (1) with the adhesive hydrogel obtained in step (2) to obtain an adhesive hydrogel / carbon fiber felt composite material.

[0080] (4) Spraying a 10 wt % lithium chloride water / ethanol solution (the solvent is a mixed solvent of water and ethanol, wherein the ethanol accounts for 20%) on one side of the carbon fiber felt of the adhesive hydrogel / carbon fiber felt composite material obtained in step (3), the loading amount of lithium chloride on the carbon fiber felt being 1.3 g·g -1 , heating at 80° C. for 3 h for drying, and then fully adsorbing for 12 h at 70% ambient humidity to obtain the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material.

[0081] Example 2

[0082] A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material comprises the following steps:

[0083] (1) The carbon fiber felt is needle-punched with a needle-punching density of 34 needles / cm 2 , a high out-of-plane orientation carbon fiber felt with a thickness of 3 mm was obtained.

[0084] (2) dissolving acrylic acid and chitosan quaternary ammonium salt (molar ratio of 15:1) in a mixed solvent of glycerol and water (glycerol accounts for 25%), stirring for 30 minutes to obtain a mixed solution; adding carbon nanotubes, ammonium persulfate and methylenebisacrylamide to the mixed solution, stirring for 15 minutes to obtain a mixed solution to be polymerized; wherein the mass ratio of carbon nanotubes to the mixed solution is 0.2:100, the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt to ammonium persulfate is 1:0.001, and the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt to methylenebisacrylamide is 1:0.001; pouring the mixed solution to be polymerized into a mold, heating at 70°C for 6 hours, and obtaining an adhesive hydrogel with a thickness of 1 mm.

[0085] (3) Compounding the carbon fiber felt with high out-of-plane orientation obtained in step (1) with the adhesive hydrogel obtained in step (2) to obtain an adhesive hydrogel / carbon fiber felt composite material.

[0086] (4) Spraying a 20 wt % lithium chloride water / ethanol solution (the solvent is a mixed solvent of water and ethanol, wherein the ethanol accounts for 40%) on one side of the carbon fiber felt of the adhesive hydrogel / carbon fiber felt composite material obtained in step (3), the loading amount of lithium chloride on the carbon fiber felt being 1.4 g·g -1 , heating at 90° C. for 2 hours for drying, and then fully adsorbing for 12 hours at 70% ambient humidity to obtain the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material.

[0087] Figure 2 The scanning electron microscope (SEM) image and energy dispersive X-ray spectroscopy (EDS) image of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 are shown in FIG. Figure 2 It can be seen that the adhesive hydrogel is tightly bonded to the carbon fiber felt with high out-of-plane orientation, and the hygroscopic salt is evenly distributed on the carbon fiber felt.

[0088] Rheological tests were performed on the adhesive hydrogels. Figure 3 The rheological diagram of the adhesive hydrogel in Example 2 as a function of shear frequency and temperature. Figure 3 As can be seen in Figure a, within the test frequency range (0.1-100rad / s), the storage modulus (G′) is significantly higher than the loss modulus (G″), indicating that a stable elastic network is formed inside the hydrogel. G′ and G″ increase with frequency and have a slight frequency dependence, and the mechanical strength inside the hydrogel increases. In addition, Figure 3 As can be seen in figure b, when the temperature increases from 25°C to 120°C, the G′ of the hydrogel is always higher than G″, which proves that the hydrogel can maintain a stable solid elastic structure within the above temperature range.

[0089] The adhesion of the adhesive hydrogel / highly hygroscopic carbon fiber felt composites was tested. Figure 4 The figure shows the adhesion test results of the adhesive hydrogel / high hygroscopic carbon fiber felt composite material prepared in Example 2 to different base materials. The adhesive hydrogel / high hygroscopic carbon fiber felt composite material before and after moisture absorption shows super high adhesion to a variety of adherends. In addition, the adhesive hydrogel / high hygroscopic carbon fiber felt composite material with a size of 15mm×15mm fits tightly to various adherends and can lift an object of 200g. The results show that before and after moisture absorption, the adhesive hydrogel / high hygroscopic carbon fiber felt composite material can maintain strong adhesion on the substrate, which can reduce the interfacial thermal resistance with the battery, and is conducive to stable evaporative cooling performance. Figure 5 This is a graph showing the environmental stability test results of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2. Figure 5 As shown, due to the presence of glycerol and lithium chloride, the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material exhibits excellent structural stability both at ultra-low temperature of -20°C and high temperature of 80°C.

[0090] In order to explore the effect of the hygroscopic salt loading on the carbon fiber felt on the hygroscopicity, a high out-of-plane orientation hygroscopic carbon fiber felt was prepared. The preparation method was as follows: a water / ethanol solution of lithium chloride with a concentration of 20 wt % (the solvent is a mixed solvent of water and ethanol, wherein ethanol accounts for 40%) was sprayed on the high out-of-plane orientation carbon fiber felt prepared in Example 2 under a relative humidity of 70%. The loading amounts of lithium chloride on the carbon fiber felt were 0.6, 1.0, and 1.4 g·g, respectively. -1 , heating at 90° C. for 2 hours for drying, and then fully adsorbing for 12 hours at 70% ambient humidity to obtain the highly out-of-plane oriented hygroscopic carbon fiber felt.

[0091] Figure 6 The hygroscopicity test results of the high out-of-plane orientation carbon fiber felt prepared in Example 2 at different hygroscopic salt loadings are shown in Figure 2. As the hygroscopic salt loading increases, the hygroscopicity of the hygroscopic carbon fiber felt increases. When the hygroscopic salt loading is 1.4 g·g -1 Considering that too much hygroscopic salt load will block the pores of the fiber felt and affect the hygroscopic performance, 1.4g·g -1 The hygroscopic salt loading was taken as the optimal parameter.

[0092] The hygroscopicity of hygroscopic carbon fiber felt with high out-of-plane orientation was tested. Figure 7 It is a hygroscopic carbon fiber felt with high out-of-plane orientation (hygroscopic salt loading is 1.4 g·g -1) Hygroscopicity data at different ambient humidity. When the relative ambient humidity was 90%, 70% and 50%, the high out-of-plane orientation hygroscopic carbon fiber felt showed 2.34, 1.64 and 1.05 g·g in 12 hours, respectively. -1 High water absorption. Even in a 30% dry environment, it still maintains 0.65g·g -1 High water absorption. The reason why the high out-of-plane orientation hygroscopic carbon fiber felt has high hygroscopicity without leakage is that the synergistic effect of the three-dimensional fiber skeleton structure between the oriented fiber bundles and the planar carbon fiber mesh layer makes the water adsorbed by the hygroscopic salt particles bound in each fiber skeleton structure. The large number of longitudinal fiber bundles in the high out-of-plane orientation hygroscopic carbon fiber felt contributes to the stable transfer of the interface fluid and avoids leakage caused by the concentrated distribution of water.

[0093] Compared with the hygroscopic properties of high out-of-plane oriented hygroscopic carbon fiber felt, Figure 8 This is a data diagram of the hygroscopicity of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 under different ambient humidity conditions. Figure 8 As shown, the adsorption equilibrium curve of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material shows a relatively low saturated moisture absorption performance, which is due to the relatively low moisture absorption efficiency of the hydrogel. Fig. 9 This is a graph showing the desorption properties of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared in Example 2 under different ambient humidity conditions. Fig. 9 As shown, the desorption rate of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material that absorbs moisture under 70% RH conditions is as high as 60% at 50°C; at 90°C, the adsorbed moisture is completely released within 2 hours, with fast desorption kinetics.

[0094] The high out-of-plane orientation hygroscopic carbon fiber felt (hygroscopic salt loading of 1.4 g·g) prepared in Example 2 was tested by a contact angle meter. -1 )'s surface and the peeling surface's wettability to water. Fig.10 The contact angle test diagram of the surface and peeling surface of the high out-of-plane orientation hygroscopic carbon fiber felt prepared in Example 2 and the leakage resistance test result diagram of the high out-of-plane orientation hygroscopic carbon fiber felt are shown in FIG. Fig.10 As shown in Figure a, the carbon fiber felt with high out-of-plane orientation has super hydrophobic properties. After being compounded with hygroscopic salt, the surface of the carbon fiber felt is still highly hydrophobic (136.5°), while the surface of the fiber felt peeling layer is extremely hydrophilic (0°). This internal hydrophilic and external hydrophobic property allows the hygroscopic salt solution to be stored in a matrix with high porosity, strong capillary force and hydrophilicity, thus avoiding the leakage of the hygroscopic salt solution. Fig.10As shown in b, the highly out-of-plane oriented hygroscopic carbon fiber felt that has been saturated with moisture in a relative humidity environment of 70% is placed on filter paper. It can be observed that there is no obvious liquid seepage on the filter paper, which proves that the highly out-of-plane oriented hygroscopic carbon fiber felt has good anti-leakage properties, which reduces the risk of corrosion to the battery due to leakage in practical applications.

[0095] Example 3

[0096] A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material is substantially the same as that of Example 2, except that in step (1), the needle punching density is 20 needles / cm 2 .

[0097] Example 4

[0098] A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material is substantially the same as that of Example 2, except that in step (1), the needle punching density is 27 needles / cm 2 .

[0099] Example 5

[0100] A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material is substantially the same as that of Example 2, except that in step (1), the needle punching density is 41 needles / cm 2 .

[0101] Fig.11 This is a distribution diagram of surface needle punching points of carbon fiber felt at different needle punching densities in Examples 2-5.

[0102] In order to more intuitively observe the improvement of the fiber orientation degree outside the carbon fiber felt surface by needle punching treatment, the carbon fiber felt was peeled off from the layers, and the fiber orientation structure on the surface of the peeled carbon fiber felt was observed using the Keyence 3D profile observer. Fig.12 shown. Fig.12 The interlayer peeling surface morphology and corresponding 3D contour diagram of the carbon fiber felts at different needle punching densities of Examples 2-5 show that the vertically oriented carbon fibers are distributed on the surface of the fiber felts. 2 ) increases, the degree of traction on the fibers in the thickness direction under the action of needle punching is higher, and the more obvious the needle-punched fiber bundles along the thickness of the carbon fiber felt are.

[0103] Carbon fiber felt is a three-dimensional structure formed by producing carbon fiber bundles by vertically passing carbon fiber through horizontally arranged carbon fiber layers during the needle punching process. Therefore, the thermal conductivity of carbon fiber felt has obvious anisotropy. Fig.13 The hygroscopic carbon fiber felts (hygroscopic salt loading of 1.4 g·g) at different needle punching densities in Example 2-5 are shown in FIG. -1 ) thermal conductivity diagram, such as Fig.13 As shown, at a needle density of 20 thorns / cm 2 When the needle density increases to 41 needles / cm 2 When the out-of-plane thermal conductivity is increased to 0.97W / m·K, this is because the needle punching effect improves the fiber orientation in the thickness direction of the carbon fiber felt and the density of the carbon fiber bundles. The increase in out-of-plane thermal conductivity helps to quickly transfer heat from the battery surface and promote efficient thermal management of the battery.

[0104] In order to further explore the effect of needle puncture on the thermal conductivity of carbon fiber felt, pure carbon fiber felt was wrapped on the battery surface, and the change in battery surface temperature during 10C discharge was tested. Fig.14 The heat dissipation data of carbon fiber felts at different needling densities of Examples 2-5 are shown in FIG. Fig.14 As shown in the figure, during the 10C rate discharge process, the battery was discharged within 6 minutes. With the increase of the needle puncture density, the heat dissipation effect of pure carbon fiber felt on lithium batteries became more obvious, and the temperature of the battery dropped from 77.5℃ to 69.5℃. This is because the needle puncture improves the high thermal conductivity of the carbon fiber felt, which can accelerate the transfer of heat on the battery surface and has a certain heat dissipation effect on the lithium battery.

[0105] The evaporation and heat dissipation performance of the battery was tested after the carbon fiber felts with different needle punching densities were subjected to moisture absorption treatment. The specific operation of the moisture absorption treatment was as follows: a water / ethanol solution of lithium chloride with a concentration of 20wt% (the solvent is a mixed solvent of water and ethanol, wherein ethanol accounts for 40%) was sprayed on the carbon fiber felt with high out-of-plane orientation prepared in Example 2-5, and the loading amount of lithium chloride on the carbon fiber felt was 1.4g·g -1 , heated at 90°C for 2h for drying, and then fully adsorbed at 70% ambient humidity for 12h to obtain a hygroscopic carbon fiber felt with a high out-of-plane orientation.

[0106] Fig.15 The heat dissipation data of the hygroscopic carbon fiber felt at different needle-punching densities in Example 2-5 show that the battery temperature is significantly reduced after being wrapped with the high out-of-plane orientation hygroscopic carbon fiber felt compared to the heat dissipation of the pure carbon fiber felt. 2 The temperature of the battery wrapped with high-hygroscopic carbon fiber felt with high needle-punched density was reduced to 59.6, 56.1, 54.7, and 53.6°C, respectively, which significantly reduced the heating rate and maximum temperature of the battery. It was confirmed that increasing the needle-punching density can greatly improve the heat dissipation effect of the material on the battery and effectively reduce the risk of thermal runaway of the battery. However, excessive needle-punching will greatly reduce the strength of the carbon fiber felt, such as Fig.16is the breaking strength of carbon fiber felt with different needle punching density. When the needle punching density is 41 needles / cm 2 When the tensile strength of carbon fiber felt is greatly reduced, therefore, 34 thorns / cm 2 The acupuncture density is the optimal parameter.

[0107] Example 6

[0108] A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material comprises the following steps:

[0109] (1) The carbon fiber felt is needle-punched with a needle-punching density of 36 needles / cm 2 , a high out-of-plane orientation carbon fiber felt with a thickness of 3 mm was obtained.

[0110] (2) dissolving acrylic acid and chitosan quaternary ammonium salt (molar ratio of 20:1) in a mixed solvent of glycerol and water (glycerol accounts for 35%), stirring for 20 minutes to obtain a mixed solution; adding carbon nanotubes, ammonium persulfate and methylenebisacrylamide to the mixed solution, stirring for 20 minutes to obtain a mixed solution to be polymerized; wherein the mass ratio of carbon nanotubes to the mixed solution is 0.2:100, the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt to ammonium persulfate is 1:0.002, and the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt to methylenebisacrylamide is 1:0.002; pouring the mixed solution to be polymerized into a mold, heating at 80°C for 5 hours, and obtaining an adhesive hydrogel with a thickness of 1.5 mm.

[0111] (3) Compounding the carbon fiber felt with high out-of-plane orientation obtained in step (1) with the adhesive hydrogel obtained in step (2) to obtain an adhesive hydrogel / carbon fiber felt composite material.

[0112] (4) Spraying a 30 wt % lithium chloride water / ethanol solution (the solvent is a mixed solvent of water and ethanol, wherein the ethanol accounts for 60%) on one side of the carbon fiber felt of the adhesive hydrogel / carbon fiber felt composite material obtained in step (3), the loading amount of lithium chloride on the carbon fiber felt being 1.5 g·g -1 , heating at 80° C. for 3 h for drying, and then fully adsorbing for 10 h at 90% ambient humidity to obtain the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material.

[0113] In order to evaluate the heat dissipation effect of batteries using adhesive hydrogel / highly hygroscopic carbon fiber felt composites, Fig.17Schematic diagram of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material wrapped lithium battery prepared in Example 2. The temperature change of commercial lithium-ion battery (18650-3.7V / 2.0AH) with or without adhesive hydrogel / highly hygroscopic carbon fiber felt composite material wrapped at an ultra-high discharge rate of 10C was tested under an environment of 25°C and 70% RH. A k-type thermocouple was placed on the battery surface near the positive electrode to monitor the battery temperature change.

[0114] Fig.18 The temperature change curves of the batteries wrapped with carbon fiber felt, adhesive hydrogel with / without carbon nanotubes added (adhesive hydrogel-without carbon nanotubes and adhesive hydrogel-with carbon nanotubes), highly hygroscopic carbon fiber felt and adhesive hydrogel / highly hygroscopic carbon fiber felt composite material at a discharge rate of 10C in Example 2, compared with the bare battery (the highest temperature is 77.5°C) and the battery wrapped with pure carbon fiber felt (the highest temperature is 70.7°C), at an ultra-high discharge rate of 10C, the temperature of the battery wrapped with adhesive hydrogel with and without added carbon nanotube thermal conductive material is reduced to 63.4°C and 65.7°C, respectively, indicating that the adhesive hydrogel has excellent evaporative cooling performance for the battery, and the addition of carbon-based thermal conductive material enhances the thermal conductivity of the hydrogel, which can further improve its heat dissipation. At the same time, the temperature of the battery wrapped by the highly out-of-plane oriented hygroscopic carbon fiber felt was reduced to 54.7°C, and the temperature of the battery wrapped by the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material was controlled below 50°C, and the maximum temperature difference reached 28.3°C, indicating that the synergistic effect of the adhesive hydrogel and the highly hygroscopic carbon fiber felt makes the adhesive hydrogel / highly hygroscopic carbon fiber felt have an excellent heat dissipation effect on the battery.

[0115] Fig.19 The temperature change curves of batteries wrapped and unwrapped with the adhesive hydrogel / highly hygroscopic carbon fiber felt composite materials prepared in Example 2 at different discharge rates are as follows. At different discharge rates, the adhesive hydrogel / highly hygroscopic carbon fiber felt composite materials show obvious cooling effect on the batteries.

[0116] Fig. 20 This is a comparison chart of the evaporative cooling efficiency of the adhesive hydrogel / high hygroscopic carbon fiber felt battery heat dissipation material prepared in Example 2 and the composite material in the prior art for batteries at different discharge rates. It can be seen that the adhesive hydrogel / high hygroscopic carbon fiber felt composite material prepared by the present invention has excellent heat dissipation performance for batteries at different discharge rates, which is significantly higher than other reported evaporative cooling composite materials for batteries. Fig.21The temperature change curve of the battery wrapped and unwrapped with the adhesive hydrogel / high hygroscopic carbon fiber felt composite prepared in Example 2 during 100 cycles of charge and discharge was shown. The battery surface temperature was monitored in real time under 100 cycles of 1C charge and 10C high rate discharge conditions. During the 100 charge and discharge cycles, the maximum temperature of the battery wrapped with the adhesive hydrogel / high hygroscopic carbon fiber felt composite was significantly lower than that of the bare battery, confirming the excellent heat dissipation ability of the adhesive hydrogel / high hygroscopic carbon fiber felt composite in long-term applications. The excellent cycle performance of the adhesive hydrogel / high hygroscopic carbon fiber felt composite is attributed to its ability to spontaneously absorb moisture during non-working hours.

[0117] Fig. 22 This is the flame retardancy test result of the adhesive hydrogel / high hygroscopic carbon fiber felt composite material prepared in Example 2 under flame combustion. The flame retardancy of the adhesive hydrogel / high hygroscopic carbon fiber felt composite material was tested, and it maintained excellent non-flammability after being exposed to high-temperature flame for 2 minutes. This excellent performance is attributed to the non-flammability of the carbon fiber felt, which can effectively slow down the spread of thermal runaway and provide critical time for taking emergency measures.

[0118] Fig.23 The thermogravimetric diagram of the adhesive hydrogel / high hygroscopic carbon fiber felt composite material, high out-of-plane orientation carbon fiber felt and adhesive hydrogel prepared in Example 2 under air atmosphere, and the decomposition temperature of the adhesive hydrogel / high hygroscopic carbon fiber felt composite material was determined by thermogravimetric analysis. In addition to desorbing water, the adhesive hydrogel / high hygroscopic carbon fiber felt composite material began to decompose at 210°C, which shows that it has good thermal stability and can desorb water in such a wide temperature range.

[0119] The present invention improves the out-of-plane thermal conductivity of the hygroscopic carbon fiber felt by increasing the fiber orientation in the out-of-plane direction of the carbon fiber felt through needle punching treatment, thereby improving the heat dissipation performance of the hygroscopic carbon fiber felt with a high out-of-plane orientation; the present invention utilizes a high thermal conductivity and strong adhesion hydrogel to composite with a high out-of-plane orientation hygroscopic carbon fiber felt, thereby reducing the interfacial thermal resistance and giving the material excellent heat dissipation performance.

[0120] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing an adhesive hydrogel / highly hygroscopic carbon fiber felt composite material, characterized in that: The following steps are involved: (1) performing a needle punching treatment on the carbon fiber felt to obtain a carbon fiber felt in an out-of-plane direction; (2) compounding the adhesive hydrogel with the carbon fiber felt in the out-of-plane direction obtained in step (1) to obtain an adhesive hydrogel / carbon fiber felt composite material; (3) coating a hygroscopic salt solution on one side of the carbon fiber felt of the adhesive hydrogel / carbon fiber felt composite material obtained in step (2), drying it and then subjecting it to a hygroscopic treatment to obtain the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the needle punching density of the carbon fiber felt in the out-of-plane direction is 20-41 needles / cm 2 .

3. The preparation method according to claim 1, characterized in that: In step (2), the method for preparing the adhesive hydrogel comprises the following steps: S1. Dissolving acrylic acid and chitosan quaternary ammonium salt in glycerol or a mixed solvent of an ionic liquid and water to obtain a mixed solution; S2. Adding a carbon-based thermally conductive filler, a thermal initiator and a cross-linking agent to the mixed solution obtained in step (1), performing a heating polymerization reaction, and obtaining the adhesive hydrogel.

4. The preparation method according to claim 3, characterized in that: In S1, the molar ratio of acrylic acid to chitosan quaternary ammonium salt is (10-20):

1.

5. The preparation method according to claim 3, characterized in that: In S2, the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt in the mixed solution to the thermal initiator is 1:(0.001-0.002), and the molar ratio of the total amount of acrylic acid and chitosan quaternary ammonium salt in the mixed solution to the crosslinking agent is 1:(0.001-0.002).

6. The preparation method according to claim 3, characterized in that: In S2, the mass ratio of the carbon-based thermally conductive filler to the mixed solution is (0.1-0.2):

100.

7. The preparation method according to claim 1, characterized in that: In step (3), the hygroscopic salt loading on the carbon fiber felt is 1.3-1.5 g·g -1 .

8. The preparation method according to claim 1, characterized in that: In step (3), the moisture absorption treatment is performed at an ambient humidity of 70 to 90%.

9. The adhesive hydrogel / highly hygroscopic carbon fiber felt composite material prepared by the method according to any one of claims 1 to 8.

10. Use of the adhesive hydrogel / highly hygroscopic carbon fiber felt composite material according to claim 9 in the field of heat dissipation of electronic devices.